HIV-1 vaccine-induced immunity in the test-of-concept Step Study: a case–cohort analysis - McElrath, M Juliana; De Rosa, Stephen C; Moodie, Zoe; Dubey, Sheri; Kierstead, Lisa; Janes, Holly; Defawe, Olivier D; Carter, Donald K; Hural, John; Akondy, Rama; Buchbinder, Susan P; Robertson, Michael N; et al. (The Lancet (British edition), 2008)
In the Step Study, the MRKAd5 HIV-1 gag/pol/nef vaccine did not reduce plasma viraemia after infection, and HIV-1 incidence was higher in vaccine-treated than in placebo-treated men with pre-existing adenovirus serotype 5 (Ad5) immunity. We assessed vaccine-induced immunity and its potential contributions to infection risk. To assess immunogenicity, we characterised HIV-specific T cells ex vivo with validated interferon-γ ELISPOT and intracellular cytokine staining assays, using a case–cohort design. To establish effects of vaccine and pre-existing Ad5 immunity on infection risk, we undertook flow cytometric studies to measure Ad5-specific T cells and circulating activated (Ki-67+/BcL-2lo) CD4+ T cells expressing CCR5. We detected interferon-γ-secreting HIV-specific T cells (range 163/106 to 686/106 peripheral blood mononuclear cells) ex vivo by ELISPOT in 77% (258/354) of people receiving vaccine; 218 of 354 (62%) recognised two to three HIV proteins. We identified HIV-specific CD4+ T cells by intracellular cytokine staining in 58 of 142 (41%) people. In those with reactive CD4+ T cells, the median percentage of CD4+ T cells expressing interleukin 2 was 88%, and the median co-expression of interferon γ or tumor necrosis factor α (TNFα), or both, was 72%. We noted HIV-specific CD8+ T cells (range 0·4–1·0%) in 117 of 160 (73%) participants, expressing predominantly either interferon γ alone or with TNFα. Vaccine-induced HIV-specific immunity, including response rate, magnitude, and cytokine profile, did not differ between vaccinated male cases (before infection) and non-cases. Ad5-specific T cells were lower in cases than in non-cases in several subgroup analyses. The percentage of circulating Ki-67+BcL-2lo/CCR5+CD4+ T cells did not differ between cases and non-cases. Consistent with previous trials, the MRKAd5 HIV-1 gag/pol/nef vaccine was highly immunogenic for inducing HIV-specific CD8+ T cells. Our findings suggest that future candidate vaccines have to elicit responses that either exceed in magnitude or differ in breadth or function from those recorded in this trial. National Institute of Allergy and Infectious Diseases, US National Institutes of Health; and Merck Research Laboratories.